What Maisie knew [videorecording (DVD)] - McGehee, Scott; Siegel, David; Moore, Julianne; Coogan, Steve; Skarsgård, Alexander; Vanderham, Joanna; Aprile, Onata; James, Henry, 1843-1916 (Millennium Entertainment, 2013)
Tells the story of Maisie, a captivating little girl struggling for grace in the midst of her parents' bitter custody battle. Told through her eyes, Maisie navigates this ever-widening turmoil with a six-year-old's innocence, charm and generosity of spirit.